2017
DOI: 10.1002/brb3.689
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow evaluation of intensive rosuvastatin therapy in stroke/transient ischemic attack patients with intracranial arterial atherosclerotic stenosis study: Rationale and design

Abstract: IntroductionThe risk of recurrent stroke is high in patients with intracranial atherosclerotic stenosis (ICAS). Statin use has been demonstrated to decrease the incidence of stroke by reducing atherosclerotic plaque burden. However, its effect on the hemodynamic situation and cerebral perfusion status has not yet been validated. With the use of computed tomography perfusion (CTP), we aim to evaluate the impact of Rosuvastatin on cerebral hemodynamic changes, as well as the downstream perfusion.MethodCerebral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Symptomatic intracranial atherosclerosis refers to ischemic stroke or transient ischemic attack occurring in the stenosis area of the supplying artery [1]. It is well established that the progression of the intracranial atherosclerotic disease will decrease blood perfusion and increase the risk of cerebral ischemic events [2][3][4][5][6]. During the progression of atherosclerotic cerebrovascular disease, the compensatory system can be initiated through the collateral circulation to preserve perfusion and stabilize cerebral blood flow [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Symptomatic intracranial atherosclerosis refers to ischemic stroke or transient ischemic attack occurring in the stenosis area of the supplying artery [1]. It is well established that the progression of the intracranial atherosclerotic disease will decrease blood perfusion and increase the risk of cerebral ischemic events [2][3][4][5][6]. During the progression of atherosclerotic cerebrovascular disease, the compensatory system can be initiated through the collateral circulation to preserve perfusion and stabilize cerebral blood flow [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Carotid atherosclerosis is a major cause of stroke and is associated with high mortality and morbidity globally 1‐3 . Atherosclerotic lesion progression leads to plaque rupture, arterial stenosis, and/or occlusion, which may cause ischemic events due to atheroembolization or hypoperfusion 4 . Luminal narrowing through angiographic approaches, such as Doppler ultrasound and CT angiography, have been used clinically to evaluate severity of carotid atherosclerosis but recent studies have shown its limitations in identifying high‐risk plaques that may cause clinical events and may miss potential embolic sources of carotid atherosclerosis and miscategorize the etiology of stroke 5‐7 …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Atherosclerotic lesion progression leads to plaque rupture, arterial stenosis, and/or occlusion, which may cause ischemic events due to atheroembolization or hypoperfusion. 4 Luminal narrowing through angiographic approaches, such as Doppler ultrasound and CT angiography, have been used clinically to evaluate severity of carotid atherosclerosis but recent studies have shown its limitations in identifying high-risk plaques that may cause clinical events and may miss potential embolic sources of carotid atherosclerosis and miscategorize the etiology of stroke. [5][6][7] Vessel wall imaging (VWI) with MRI of the carotid artery has been recognized to be able to identify high-risk atherosclerotic lesions and may improve diagnosis sensitivity and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis is a major cause of cardio-and cerebrovascular disease mortality and morbidity globally [1][2][3]. Plaque progression leads to arterial stenosis and/or occlusion, which may cause downstream ischemic events due to atherothrombosis or hypoperfusion [4]. As a subset of atherosclerosis, intracranial atherosclerosis accounts for about 30-50% and 10% of cerebrovascular ischemic events in Asian and Caucasian populations, respectively [5].…”
Section: Introductionmentioning
confidence: 99%